Fragile X syndrome: economic burden and health‐related quality of life of patients and caregivers in France. (15th September 2015) - Chevreul, K.; Berg Brigham, K.; Brunn, M.; des Portes, V.; ,
Abstract: Background: Fragile X syndrome (FXS) is the main hereditary cause of intellectual disability. Although the associated burden appears to be considerable, to date no study has comprehensively assessed the cost incurred because of FXS, including its specific impact on health‐related quality of life and the burden on caregivers using standardised quantitative tools. The aim of this article is to provide data in order to increase awareness of the repercussions of FXS on patients and caregivers as well as on the health and social care systems in France. Methods: A retrospective cross‐sectional study was carried out on 145 patients recruited through Le Goëland X‐Fragile and Mosaïques, the French FXS patient associations. Data on their demographic characteristics and resource use were obtained from an online questionnaire, and costs were estimated by a bottom‐up approach. The EQ‐5D health questionnaire was used to measure patients' and caregivers' health‐related quality of life. Perceived burden of care was measured using the Zarit Caregiver Burden Interview. The Barthel index, a non‐utility‐based assessment, was used to measure patients' level of dependence. Results: The annual total direct cost of FXS was estimated at €25 800 per patient. The main contributors were informal care provided by the main caregiver (€10 500) and social services (€8400). Healthcare costs, estimated at €2700, represented only a minor share. Mean EQ‐5D utility scores were 0.49 for patients and 0.75 for caregivers. The mean burden for caregivers as measured by the Zarit Caregiver Burden Interview was 39.9. Conclusions: Fragile X syndrome requires significant resources that are mainly of a non‐medical nature and are higher for children than for adults. Compared with related diseases, it constitutes a particularly high burden for caregivers. Using a bottom‐up approach and a wide range of standardised measures, this study underscores the need for greater awareness of the burden of FXS as well as an assessment of new and existing interventions to address it.